Control of cardiac ryanodine receptor by sarcoplasmic reticulum luminal Ca(2+) - Jones, Peter P. (J Gen Physiol, 2017)
Jones et al. propose that SR luminal Ca(2+) regulates RyR2 activity via a luminal Ca(2+) sensor distinct from the cytosolic Ca(2+) sensor.